Supplementing rumen‐protected methionine to lactating multiparous dairy cows did not improve reproductive performance. Issue 9 (6th August 2019) - Süss, David; Iwersen, Michael; Schweinzer, Vanessa; Gusterer, Erika; Kanz, Peter; Krieger, Stefanie; Pothmann, Harald; Wagener, Karen; Hoelker, Michael; Tesfaye, Dawit; Schellander, Karl; Helmbrecht, Ariane; et al.
Abstract: There is evidence that supplementing methionine has positive effects on uterine environment, oocyte quality and embryo development in cattle. Thus, the objective of this study was to evaluate reproductive traits of cows supplemented with rumen‐protected methionine (RPM) during early to mid‐lactation in comparison with an untreated control group (CON). An additional focus was on the effect of puerperal diseases on reproductive performance parameters in RPM‐supplemented group MET and in CON. A total of 1, 709 multiparous Holstein‐Friesian cows were enrolled in this field trial conducted on a commercial dairy farm in Slovakia. Cows were allocated at approximately 12 days post‐partum (dpp) to either CON or MET, the latter supplemented with 25.0 g–27.2 g RPM per cow per day incorporated into the total mixed ration (TMR) until leaving the study pen at approximately 140 dpp. The amount of RPM was calculated based on individual feed ingredients analysis and adjusted during the study period when TMR changed. Cows were monitored during the post‐partum period by vaginal examination (day 5 pp), measuring of beta‐hydroxybutyrate in blood (3, 5, and 8 dpp) and by vaginal examination, uterine cytology and measuring of back fat thickness by ultrasound (all at 31 ± 3 dpp). Compared with CON, cows supplemented with RPM did not show better reproduction performance parameters (first service submission rate, days to first service, conception risk, days open 140). Results from binary logistic regression model for the risk of conception showed that metritis had a significant effect, but the supplementation of methionine had not. Results of Cox regression analysis for the odds of conception within 140 dpp revealed only metritis and clinical endometritis as significant factors. In conclusion, supplementation of RPM had no beneficial effect on reproductive performance in this study farm compared with an untreated control group.